The representation of space in the brain - Grieves, Roddy M.; Jeffery, Kate J. (Behavioural processes, 2017)
[Display omitted] •Animals appear to possess an internal representation of space or ‘cognitive map’.•Three neurons are thought to form the basis of this map: place, head direction and grid cells.•There are many other, less well understood types of spatially sensitive neuron.•A systems-level understanding of the brain requires that we also understand these neurons.•Here we review the spatially sensitive cells that are not place, head direction or grid cells. Animals can navigate vast distances and often display behaviours or activities that indicate a detailed, internal spatial representation of their surrounding environment or a ‘cognitive map’. Over a century of behavioural research on spatial navigation in humans and animals has greatly increased our understanding of how this highly complex feat is achieved. In turn this has inspired half a century of electrophysiological spatial navigation and memory research which has further advanced our understanding of the brain. In particular, three functional cell types have been suggested to underlie cognitive mapping processes; place cells, head direction cells and grid cells. However, there are numerous other spatially modulated neurons in the brain. For a more complete understanding of the electrophysiological systems and behavioural processes underlying spatial navigation we must also examine these lesser understood neurons. In this review we will briefly summarise the literature surrounding place cells, head direction cells, grid cells and the evidence that these cells collectively form the neural basis of a cognitive map. We will then review literature covering many other spatially modulated neurons in the brain that perhaps further augment this cognitive map.